2002
DOI: 10.1034/j.1399-0004.2002.620409.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel R75Q mutation in the GJB2 gene causes autosomal dominant hearing loss and palmoplantar keratoderma in a Turkish family

Abstract: Dominant mutations in the GJB2 gene encoding connexin 26 (Cx26) can cause non-syndromic hearing impairment alone or in association with palmoplantar keratoderma (PPK). We have identified the novel G224A (R75Q) mutation in the GJB2 gene in a four-generation family from Turkey with autosomal dominant inherited hearing impairment and PPK. The age of onset and progression of hearing loss were found to be variable among affected family members, but all of them had more severe impairment at higher hearing frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
3
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 23 publications
3
55
3
2
Order By: Relevance
“…In these cases an AD mode of inheritance was observed, and in some subjects the HI was associated with palmoplantar keratoderma [58,59]. An AD mode of inheritance appeared probable in the present study in which 10 members of a family with no reported consanguinity had HI, three of whom also had palmoplantar keratoderma.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In these cases an AD mode of inheritance was observed, and in some subjects the HI was associated with palmoplantar keratoderma [58,59]. An AD mode of inheritance appeared probable in the present study in which 10 members of a family with no reported consanguinity had HI, three of whom also had palmoplantar keratoderma.…”
Section: Discussionsupporting
confidence: 46%
“…The p.R75Q (OMIM, img 121011.0026) mutation has variously been described in subjects with HI in Turkey [58], France [59], a family of Russian origin [60], and in 1/207 patients in Brazil [8]. In these cases an AD mode of inheritance was observed, and in some subjects the HI was associated with palmoplantar keratoderma [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these cell lines clearly showed functional differences in neurobiotin (NB) transfer analysis ( Figure 4, I, J, O, and P) depending on the level of GJP disruption (Figure 4, F, G, L, and M), even when mutations at the same amino acid in CX26 were used (i.e., R75W and R75Q, which also cause hereditary deafness; ref. 24). The cells with smaller GJPs had less extensive NB dye transfer as compared with cells with larger GJPs (Figure 4, H-Q).…”
Section: Resultsmentioning
confidence: 99%
“…The most prevalent nonsense mutation W24X truncating Cx26 protein (24 amino acids), was first reported in a Pakistani family [65]. The GJB2 mutations which cause syndromic HL include: delE42, [67], G12R, D50N and S17F [68], G59A [69], N54K [70], R75Q [71], R75W [72], D66H [73], G130V [74]. While autosomal dominant non-syndromic HL is caused by C202F [75], R143Q [76], W44C [77], R184Q [78], D179N [79] and G21R gene mutation.…”
Section: Page 3 Ofmentioning
confidence: 99%